Peningkatan Literasi Kesehatan Mental Santri di Pondok Pesantren Sirojul Ulum As-Sarqowi Malang - Muhammad Hilal; Abdul Wahid Purnama (Lembaga Penerbitan dan Publikasi Ilmiah, 2026)
Adolescent mental health is a crucial aspect of academic success, yet attention to this issue within Islamic boarding schools (pesantren) remains severely limited. This community service project aims to enhance mental health awareness and literacy among students (santri) at Sirojul Ulum As-Sarqowi Pesantren in Gondanglegi, Malang. The intervention method was executed in three primary stages: preparation, implementation of social advocacy utilizing interactive lectures and the